25 years of research and regulation: Is nanotechnology safe to commercialize? - Rasmussen, Kirsten; Sayre, Phil; Kobe, Andrej; Gonzalez, Mar; Rauscher, Hubert (Frontiers in Toxicology, 2025)
This paper examines the global communities’ regulatory and scientific advancements in nanotechnology and nanomaterials since 2000. It explores some similarities and differences in nanomaterial safety compared to general chemical safety. The paper provides an overview of the encountered challenges and how far they have been resolved, as well as information on how different countries’ legislators have addressed nanomaterials, including safety assessment in (new) legislation. Challenges arose due to the unique physico-chemical properties of some nanomaterials and included the lack of i) a regulatory definition, ii) applicable regulatory test methods, including methods for physico-chemical characterization and for ecotoxicological effects, as well as sample preparation and dosimetry, iii) assessment and modelling of human, especially occupational, and environmental exposure to nanomaterials, iv) quantification of nanomaterial in complex media, v) systems for collecting the data generated and ensuring FAIR (Findable, Accessible, Interoperable and Re-usable) and quality data, vi) reference nanomaterials, and vii) a frame for nanotechnology governance. The paper highlights the role of the Organisation for Economic Co-operation and Development (OECD) in building a global, regulatory understanding of nanotechnology and nanomaterials, as well as the OECD’s achievements of developing nano-specific test guidelines. The paper identifies areas, such as alternative test methods, availability of reference nanomaterials, comparable data and FAIR data, analytical tools for quantifying nanomaterials in (complex) matrices that are still under-addressed. It gives a wider perspective of Governance of Advanced Materials including nanomaterials, also illustrated by carbon nanotubes used in batteries for electric vehicles, to also aid their commercialization. In the EU, the policy context is moving towards a holistic governance approach embracing sustainability dimensions.